Informed consent in assisted reproductive technology: Implications for pediatric clinicians - Graham, Mary E.; Blee, Shannon; Pentz, Rebecca D.; Roebuck, Emily; Hoon, Alexander H.; Black, Mara (Developmental medicine and child neurology, 2025)
After conceiving through assisted reproductive technologies (ART), parents may present to their pediatrician with concerns related to their child's neurodevelopment, including whether their child's health may be related to their use of ART. Pediatricians may be unfamiliar with the ART process and what the families endured up to this point, resulting in difficulty counseling parents through these discussions. Before presentation to the pediatrician, parents have undergone extensive evaluation with reproductive endocrinologists. During counseling, the reproductive endocrinologist provides information on maternal and childhood risks associated with ART. However, in this rapidly evolving field, providing comprehensive, patient‐centered, informed consent is increasingly complex and counseling patients properly can be challenging. When parents have gone through the proper informed consent process, and when the pediatrician has an understanding of what this process entails, care of the child can be optimized. In this review, we discuss the complexities of the prenatal informed consent process that parents navigate before presenting to pediatricians. We emphasize the importance of these discussions and highlight ethical principles, as well as emotional, medical, legal, and financial stressors that parents face during ART, with the belief that this understanding will improve the care that pediatricians subsequently provide. Informed consent in assisted reproductive technology (ART) is a complex, multifaceted process. Given the short‐ and long‐term risks associated with ART, neurodevelopmental physicians can benefit from a better understanding of this process when evaluating patients for neurodevelopmental disability. Plain language summary: https://onlinelibrary.wiley.com/doi/10.1111/dmcn.16205